2002
DOI: 10.1046/j.1525-1314.2003.00415.x
|View full text |Cite
|
Sign up to set email alerts
|

Petrogenetic significance of orthopyroxene‐free garnet + clinopyroxene + plagioclase ± quartz‐bearing metabasites with respect to the amphibolite and granulite facies

Abstract: Orthopyroxene‐free garnet + clinopyroxene + plagioclase ± quartz‐bearing mineral assemblages represent the paragenetic link between plagioclase‐free eclogite facies metabasites and orthopyroxene‐bearing granulite facies metabasites. Although these assemblages are most commonly developed under P–T conditions consistent with high pressure granulite facies, they sometimes occur at lower grade in the amphibolite facies. Thus, these assemblages are characteristic but not definitive of high pressure granulite facies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
119
0
22

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(159 citation statements)
references
References 76 publications
18
119
0
22
Order By: Relevance
“…Stage 3 is defined by the following kelyphite -forming reaction: Grt + Cpx + Qtz = Opx + Pl (e.g., Pattison, 2003). Previous experimental work on the anorthite -enstatite system (Kushiro and Yoder, 1966) and the pseudosection calculation analyses on pyroxenitic rock from the Erzgebirge (Schmädicke, 2000) suggested that this reaction takes place in a narrow pressure range (1.4 -1.6 GPa) at relatively high T conditions (700 -1000 °C).…”
Section: Equilibrium Stages and The Pressure-temperature Pathmentioning
confidence: 99%
“…Stage 3 is defined by the following kelyphite -forming reaction: Grt + Cpx + Qtz = Opx + Pl (e.g., Pattison, 2003). Previous experimental work on the anorthite -enstatite system (Kushiro and Yoder, 1966) and the pseudosection calculation analyses on pyroxenitic rock from the Erzgebirge (Schmädicke, 2000) suggested that this reaction takes place in a narrow pressure range (1.4 -1.6 GPa) at relatively high T conditions (700 -1000 °C).…”
Section: Equilibrium Stages and The Pressure-temperature Pathmentioning
confidence: 99%
“…The assemblage, garnet + clinopyroxene + plagioclase, characterizes a transition between the granulite and eclogite facies in terms of continuous reactions that produce garnet at the expense of orthopyroxene and plagioclase with increasing pressure (e.g., O'Brien and Rötzler, 2003;Pattison, 2003). This assemblage with or without hornblende and quartz occurs in the terranes not only of high pressure granulite facies but also of amphibolite facies (e.g., Pattison, 2003).…”
Section: Geothermobarometrymentioning
confidence: 99%
“…This assemblage with or without hornblende and quartz occurs in the terranes not only of high pressure granulite facies but also of amphibolite facies (e.g., Pattison, 2003). Figure 9 compares the estimated condition with the P T estimates of metabasites possessing these assemblages for granulite, transitional amphibolite granulite and amphibolite occurrences compiled by Pattison (2003). The estimated condition is similar to those of garnet + clinopyroxene + plagioclase ± hornblende ± quartz assemblages found in terranes of the granulite facies in the world.…”
Section: Geothermobarometrymentioning
confidence: 99%
“…The granulite-facies pressure-temperature domain is subdivided into low-, intermediate-and high-P fields based on the coexistence of orthopyroxene, clinopyroxene and garnet in mafic lithologies (e.g., Spear, 1993). High-P granulites are defined by the mineral assemblage Grt +Cpx +Pl ±Hbl ±Qtz (Pattison, 2003; abbreviations follow Kretz, 1983). Opx coexists with this paragenesis in the intermediate-P field, while Grt disappears in the low-P field (Spear, 1993).…”
Section: Introductionmentioning
confidence: 99%